PENGARUH PERKEMBANGAN ANAK TERHADAP KETERGANTUNGAN GADGET (SMARTPHONE) PADA ANAK USIA 5-6 TAHUN - Mega setiawan; Eka Sulastri; Upus Piatun Khodijah (Politeknik Kesehatan Kementerian Kesehatan Banten, 2020)
The use of gadgets or smartphones is inevitable and one thing that is often overlooked is the negative effect of the radiation of the gadget itself on the user's body, especially for children. The purpose of this study was to determine the effect of children's development on gadget dependence (smartphones) in children aged 5-6 years at Al-Ikhlas Kindergarten and Amanah Guna Karya Foundation (YGK) Jatimulya Village, Sumedang Utara District in 2018. The type of research used was quantitative research with cross sectional design. Sampling in this study using nonprobability sampling with consecutive sampling method that is 33 respondents. The results showed that development in children aged 5-6 years found that children with the possibility of deviation of 15 people (45.5%) and gadget dependence (smartphone) in children aged 5-6 years found that children who have dependence on gadgets as many as 16 people (48.5%). There is an influence of children's development on gadget dependence (smartphone) in children aged 5-6 years in Al-Ikhlas Kindergarten and Amanah Guna Karya Foundation (YGK) Jatimulya Village, Sumedang Utara District in 2018 with a value of p = 0.003. It is expected that parents can increase their knowledge and minimize the use of gadgets (smartphones) to their children.